Status, Hukum,Peraturan, ,Pemerintah, ,Pengganti, Undang-Undang,Nomor, 2 Tahun, 2022, Tentang Cipta,Kerja Dalam Ketatanegaraan,Indonesia - Agung Saputra (Jurnal Ilmu Hukum, 2024)
Government Regulation in Lieu of Law (PERPPU) Number 2 of 2022 concerning Job Creation is the Indonesian government's response to facing a pressing emergency situation. This research aims to analyze whether the Perppu meets the criteria regarding the need for urgency in accordance with the principles of Indonesian constitutional law. Apart from that, this research will also examine the legal status of the Perppu in the Indonesian constitutional system. By using a normative juridical approach, this research found that Perppu Number 2 of 2022 was issued to deal with various urgent economic and investment problems, as well as to create a more conducive business climate in the midst of the pandemic. However, there is still debate regarding the validity and urgency of issuing this Perppu, as well as its impact on existing legal provisions. It is hoped that these findings will provide a deeper understanding of the legislative process and the establishment of Perppu in Indonesia, as well as the implications for law enforcement and government governance